Potential of Soy Gum Emulsification in Starter Diets for Broiler Chickens - Ouros, Caio C.; Laurentiz, A. C. [UNESP]; Pizauro, J. M. [UNESP]; Filardi, R. S. [UNESP]; Santos, L. F.J. [UNESP]; Laurentiz, R. S. [UNESP] (FapUNIFESP (SciELO), 2022)
This study evaluated the viability of using soy gum (residue from soy processing to obtain degummed oil) as an emulsifier in starter diets for broilers (1 to 21 days). For this, 600 1-day-old male broilers (Cobb® 500) were randomly assigned in a factorial arrangement (3 x 4), with three levels of gum inclusion (0, 1.25, and 2.5%) and four levels of soybean oil (0,1.3, 2.6, and 3.9%), with 5 replicates of 10 birds each. At 7, 14, and 21 days of age, we analyzed the performance parameters, pancreatic lipase activity and digestibility coefficients. Inclusion of soy gum improved (p<0.05) the performance and the digestibility coefficient of the ether extract, increased (p<0.05) the levels of AME and AMEn. The higher inclusion of gum (2.5%) as an emulsifier resulted in improved performance, showing the best values of feed conversion, with increased ether extract digestibility, increased AME content of the diets, and a lower requirement for pancreatic lipase in micelle formation.
Keywords: by-product; Emulsifier; pancreatic lipase; residue